Evaluation of practice of cross infection control for dental impressions among laboratory technicians and prosthodontists in KSA - Sedky, Nabila Ahmed (International Journal of Infection Control, 2014)
The purpose of the present study was to assess the current practice of cross infection control of dental impressions in governmental & private dental labs & prosthodontic clinics of MoH, Al-Qassim, KSA, evaluating how dentists are communicating with lab personnel about impression disinfection, and, detecting awareness about infection control practices in dental laboratories. Cross-sectional study including self-administered anonymous questionnaires. The sample included 50 dental technicians and 55 dentists in two cities. Technicians and prosthodontists were subjected to questionnaires consisting of 26 and 14 questions, respectively. Forty six questionnaires were completed for technicians and 48 for prosthodontists. More than 60.00% of technicians knew that impressions have been disinfected and 56.25% of dentists notified technicians that impressions have already been disinfected. About 64.00% of technicians had an agreed protocol between lab and clinic, and 40.74% of prosthodontists notified technicians through notes on impression bags. About 61.00% reported that all technicians in lab were vaccinated for HBV. Only 6.40% of technicians apply all protective precautions when receiving impressions. Fifty percent of the prosthodontists aren't sure that technicians disinfect impressions before pouring. About 65.00% of technicians feel that laboratories are adequately instructed for disinfection techniques of different impression materials and on contrary, 66.67% of prosthodontists didn’t feel that. Moderate communication between dental technicians and prosthodontists. The majority of dental technicians were vaccinated for HBV. Most dentists didn’t pour impressions in their clinics. Lack of communication between prosthodontists and their dental technicians was noticeable. Significant nonconformity of view between dental technicians and prosthodontics was reported.